Utang dan Pengakhiran Perjanjian Secarap Sepihak (Studi Kasus Perjanjian Konsultan PT. Garuda dan PT. Magnus - Awalia Noviyanti; Mukti Fajar Nur Dewanto (Jurnal Hukum Novelty, 2018)
This article aims to analyze the existence of the debt in reciprocal agreement between PT. Garuda and PT. Magnus, and about the termination of agreement which set aside article 1266 Civil Law unilaterally whether could cancel debt payment obligation or not. This research is normative research which observes the data that correlated to agreement, debt, act againts the law, and termination of agreement which set aside the article 1266 Civil Law. The approach of this article is statute approach which review the data that have correlation with law of agreement and termination of agreement, and case approach. It is the case of PT. Garuda and PT. Magnus. The data collection was done by library research that observing the data about law of agreement and termination of agreement. The result of research shows that there must be approval from each party in reciprocal agreement. Thus, the debt of PT. Garuda to PT. Magnus is the obligation that must be fulfilled due to PT. Magnus has worked maximally to complete its obligation. In other side, the termination of law which set aside article 1266 Civil Law is act againts the law, therefore the obligation to pay the debt must be done, in the reason of there is indemnification in act againts the law.